Meta-Analysis: An integrative approach to Islamic values in biology learning - Viina Miratun Nisa; Ria Yulia Gloria; Mujib Ubaidillah (Universitas Ahmad Dahlan, 2021)
One example of an integrative approach in learning is the integration of Islamic values in Biology learning. This article describes and analyzes the influence of Islamic values in Biology learning. The results of the study are a summary of the available empirical evidence about the effect of integrating Islamic values in Biology learning. This study uses a meta-analysis method, the articles analyzed are 15 articles that meet the requirements of 57 articles that have an integrative approach to Islamic values. The results showed that the integration of Islamic values in Biology learning had a large effect with an effect size of 3.50. For education level, the largest effect size is at the high school education level (3.74), for the provision of action the largest effect size is for the Hypno-teaching method (5.13), for the use of the dependent variable the largest effect size is on the dependent variable mastery of concepts (4.70), while for Biology material, the largest effect size is on the material of the reproductive system (5,08). The results of the research as a whole conclude that the integrative approach of Islamic values in biology learning is effective for use, especially at the high school level, in the Hypno-teaching method, in mastering concepts, and reproductive system materials.